2012
DOI: 10.1186/1479-5868-9-92
|View full text |Cite
|
Sign up to set email alerts
|

The association between sidewalk length and walking for different purposes in established neighborhoods

Abstract: BackgroundWalking in neighborhood environments is undertaken for different purposes including for transportation and leisure. We examined whether sidewalk availability was associated with participation in, and minutes of neighborhood-based walking for transportation (NWT) and recreation (NWR) after controlling for neighborhood self-selection.MethodBaseline survey data from respondents (n = 1813) who participated in the RESIDential Environment (RESIDE) project (Perth, Western Australia) were used. Respondents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 44 publications
1
48
1
1
Order By: Relevance
“…31 An approach that considers the combined benefits for health from investments in walking, cycling, and other transportation infrastructure could be used when calculating the economic impacts of these investments. 32,33 Studies appear in leading health journals (for example, The Lancet), 34 are now creating a growing body of literature on the economics of investing in cycling infrastructure, 35 sidewalks, 36 and more walkable environments.…”
Section: Study the Health-economic Impacts Of Active Living Infrastrumentioning
confidence: 99%
“…31 An approach that considers the combined benefits for health from investments in walking, cycling, and other transportation infrastructure could be used when calculating the economic impacts of these investments. 32,33 Studies appear in leading health journals (for example, The Lancet), 34 are now creating a growing body of literature on the economics of investing in cycling infrastructure, 35 sidewalks, 36 and more walkable environments.…”
Section: Study the Health-economic Impacts Of Active Living Infrastrumentioning
confidence: 99%
“…Two studies [30,64] found inconsistent results when using different analyzed geographic units. Five studies [25,30,42,58,62] found inconsistent results when using different measurements of AT. One study [48] found inconsistent relationships between land use mix and walking to different destinations.…”
Section: Inconsistent Results From Studies With Different Designsmentioning
confidence: 99%
“…Residential density [30] • Parcel level density was positively related to the frequency of walking for transport and not related to the participation in walking for transport • Area level density was not related to the frequency of walking for transport and negatively related to the participation in walking for transport Land use mix [48] • Land use mix was positively related to walking for errands • Land use mix was not related to walking to work/school Street connectivity [64] • 500-m buffer: street connectivity was positively related to walking for transport • 1000-m buffer: street connectivity was not related to walking for transport Walkability [25] • Walkability was positively related to the participation in walking for transport • Walkability was not related to the duration of walking for transport [42] • Walkability was positively related to the frequency of walking for transport • Walkability was not related to the duration of walking for transport Bicycle lane [61] • Bicycle lane was not related to cycling for transport • Bicycle network connectivity was positively related to cycling for transport Table 9. Cont.…”
Section: Built Environment Factors Reference Resultsmentioning
confidence: 99%
See 2 more Smart Citations